(untitled) (CIPEEX, 2025)
The extraction of third molars is an invasive surgery that can cause fear and anxiety in patients. This emotional state can lead to physiological changes that can hinder the clinical procedure. Therefore, methods to control this have been investigated. One therapy that has beneficial effects for anxiety control is intravascular laser blood irradiation (ILIB). The aim of this study was to evaluate the effectiveness of ILIB in controlling anxiety in patients undergoing lower third molar extraction. A randomized clinical trial was conducted with 18 patients with indications for lower third molar extraction. Participants were allocated into two groups: a control group (n = 8) that underwent placebo treatment; and an ILIB group (n = 10), which was irradiated in the region near the radial artery with a red laser (660 nm), 100 mW, continuous mode, for 30 minutes. Anxiety was assessed before and after the ILIB session using the STAI-Y questionnaire. Patients undergoing ILIB showed a significant reduction in anxiety when comparing initial and final scores. ILIB demonstrated efficacy in controlling anxiety in the participants involved.